ATTITUDES AND PRACTICES OF SMOKING AMONG MALE STUDENTS OF ADVANCED LEVEL BIOLOGY STREAM TUITION CLASSES IN AN URBAN DISTRICT IN SRI LANKA - Perera, U.; Perera, S.; Perera, M.; Jayakody, S. (My University, 2019)
Smoking has become a major public health problem worldwide, including Sri Lanka. In most of the cases initiation of smoking is seen in adolescence. A descriptive cross sectional study was conducted among male students of two selected Advanced Level Biology tuition classes in Gampaha to describe the attitudes and practices of smoking and associated factors. Two hundred male students were selected by a systematic sampling method. A self-administered questionnaire on socio-demographic data, questions to assess attitudes and practices of smoking and associated factors, was given. Chi square test was used to assess the significance and p value of < 0.05 was taken as significant. The overall prevalence of ever smoking was 16%. Among them 27.3% had smoked more than 100 cigarettes (5 packs) up to now. Seven percent were daily smokers. Majority had tried their first cigarette at the age between 14-16 years (54.5 %). Current smoking habit observed among boys was positively associated with having a close friend who is a smoker (p=0.001), father (p=0.013) and brothers (p=0.001) who are smoking and favorable home environment for smoking (p=0.001). There was no significant association between academic performance and smoking behavior (p=0.061). Anti-smoking advertisements were negatively associated with current smoking (p=0.960). About one third of ever smokers (30.3%) had a positive impact by seen pictorial health warnings on cigarette packets.
Keywords: Smoking, Adolescents, Attitudes, Practices